Literature Review on Multi-Regional Input-Output Matrices (EE-MRIO) (British Journal of Multidisciplinary and Advanced Studies, 2024)
The aim of this paper is to review the development of environmentally extended multi-regional input-output matrices (EE-MRIO) through a literature review. The EE-MRIO, developed by Wassily Leontief, reveals the interdependence of industries in an economy, using general-equilibrium models to express relationships between sectors. This article enhances the current knowledge on the subject, providing valuable insights for scholars, decision-makers, and practitioners, and offers a comprehensive overview of the models' evolution.